3(x-5)=66/11

Simple and best practice solution for 3(x-5)=66/11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-5)=66/11 equation:


x in (-oo:+oo)

3*(x-5) = 66/11 // - 66/11

3*(x-5)-(66/11) = 0

3*(x-5)-6 = 0

3*(x-5)-6 = 0

3*x-21 = 0

3*x-21 = 0

3*x-21 = 0 // + 21

3*x = 21 // : 3

x = 21/3

x = 7

x = 7

See similar equations:

| 6x+4=6(x-5) | | (3.75)*(44.5)= | | 100=8000/12 | | -2+7=13 | | 0.14(y-1)+0.18y=0.06y-0.01(40) | | 4x-4y*(-3)=0 | | x-(2x+5)=3x+13 | | -5x/6+1=5/18 | | 12-5x=48 | | 11x-6=7-2x | | (235)^1/3 | | 1-6y+3=2y+10-6y | | -9=5-(7-z) | | -6(x+5)+5=-25 | | 1(x-9)=5x-4(x-1)+43 | | 5-2(y+1)=2 | | x/14+51=55 | | -11+10=-45 | | 6(4+n)= | | 5(2+v)+36v=13v | | (1/4)/(65/12)= | | f(z)=xy^2+ix^2y | | 7.4p-2.3p+3.1=33.7 | | 8x+2x=-15 | | 7(y+8)= | | 2.1x-1.1x+8.1=-0.6 | | n/5+10n+51 | | 5v/6+7/6=112 | | 0.55x+0.4=x-2 | | 6-2(4-m)=8m-3(2m+5) | | 9x+8-4x=14-x | | 132=(t*t)-T |

Equations solver categories